Física, cuentos y poemas - Valencia M, Harol Y.; Millan, Diana A. (Revista Científica, 2011)
A didactic strategy is designed and implements across the stories and poems, as representations of the language, for the teaching of the physics. The expression across the word facilitates the comprehension and interpretation of the concepts by the students, since these try to provoke his feelings, sensations of beauty, creativity, imagination and influence, using concepts and definitions in the field of the physics. These stories and poems are presented of individual form with the concepts and theories studied during the course, then there is done a correction of these concepts, from that the student wants to express, appearing this way a projection and introjection dynamics between the student and the teacher. Being like that an investigation of exploratory and comprehensive character, of this way the study of case is the appropriate tool.